Depression among diabetic patients: a cross sectional study (Bangladesh Journal of Psychiatry, 2020)
Anxiety disorder is the most prevalent mental disorder in Bangladesh according to the estimation of The risk of depression is doubled by diabetes which is often overlooked. The aim of the cross[1]sectional study was to find out the proportion of depression and its connection with socio[1]demographic differences among diabetic patients attending in the outpatient and inpatient departments of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) hospital and the endocrine outpatient department as well as medicine inpatient department of Bangabandhu Sheikh Mujib Medical University (BSMMU) from November 2006 to September 2007. Through consecutive sampling, 390 patients suffering from diabetes for at least one year, above 18 years of age, were included in the study. A semi[1]structured questionnaire to collect socio-demographic and other relevant information, the Global Health Questionnaire 12 items (GHQ 12) for screening of psychiatric manifestation, and diagnostic and statistical manual for mental disorder (DSM) IV TR diagnostic criteria to diagnose psychiatric disorders were used. The results showed that, out of 390 respondents, 106 patients (27.2%) had depression. An association with co-occurring depression was observed in female, low level of education, low socioeconomic condition, farmers, students, housewives, unmarried, divorced and patients having family or past history of psychiatric disorders. The findings of this study will help to draw adequate attention from physicians in this issue while treating diabetic patients.Bang J Psychiatry 2020; 34(1):9-13